1996
DOI: 10.1089/mdr.1996.2.401
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Multidrug-Resistant Streptococcus pneumoniae in South Korea

Abstract: Streptococcus pneumoniae was isolated from patients with bacteremia, meningitis, pneumonia, and otitis media and used to determine susceptibility to various antibiotics. Of 105 isolates, 51% to 83% were resistant to 6 antibiotics (i.e., the percentages of resistance to penicillin, ampicillin, cephalothin, chloramphenicol, tetracycline, and erythromycin were 78%, 67%, 51%, 56%, 83%, and 58%, respectively). Also, 66 of the 105 isolates were multidrug resistant. Seventy-eight percent of multidrug-resistant strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
4
9
1
Order By: Relevance
“…Fewer comparative data are available for South Korea. In 1996, Kim et al [5] reported a value of 58% (61/105) for macrolide-resistant S. pneumoniae, in contrast with our value of 87.6%. For Japan, previous studies have reported values of 66.5% for the 1997-1998 winter season [8], while we found a prevalence of 77.9%.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Fewer comparative data are available for South Korea. In 1996, Kim et al [5] reported a value of 58% (61/105) for macrolide-resistant S. pneumoniae, in contrast with our value of 87.6%. For Japan, previous studies have reported values of 66.5% for the 1997-1998 winter season [8], while we found a prevalence of 77.9%.…”
Section: Discussioncontrasting
confidence: 87%
“…The resistance rate for South Korea (71.5%) parallels two recently reported values of 78% in 1996 [5] and 79.7% combined resistance in 1996-1997 [14], possibly indicating that a high stable rate has existed for the last four years. Since the predominance of the 23F capsular-type clone in Hong Kong in 1995 [15], all reports have indicated penicillin resistance of 50-60% [2,6,[15][16][17] (including our own value of 57.1% for 1999-2000).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the years 1999 to 2002, more than half of the isolates were penicillin nonsusceptible and one-quarter of the isolates were fully penicillin resistant and multiresistant. These rates are comparable to those obtained in studies in other Asian countries, including South Korea (2,13,16,19,29,30,31,32), Hong Kong (10,11,12,18), Taiwan (7,8,9,27), Singapore (15,28,30), Thailand (30), and Japan (30,36), but are considerably higher than those obtained in studies in other countries in this region such as China (21,35), Malaysia (25), and the Philippines (1). In a recent multicenter study of 996 clinical isolates from 11 Asian countries, including 176 isolates from blood or CSF, 18.3% showed intermediate susceptibility and 22.7% were fully resistant (30).…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of resistance to chloramphenicol (40%) is also high, even though this antibiotic was hardly administered to pediatric patients in the hospital. High frequencies of resistance to tetracycline and erythromycin were observed among the isolates, and the figures were comparable to those reported for China and South Korea (12,17). Of the 180 isolates, 28.9% were resistant to all four non-beta-lactam antibiotics tested, and the prevalence of drug-resistant S. pneumoniae in Singapore is higher than that determined from the results of a 30-center national surveillance study, which showed that the prevalence of drug-resistant S. pneumoniae was less than 18% in the United States (7).…”
supporting
confidence: 85%